Surface treatment with silicon-based nanoparticles induced during curing: Effect on durability of portland cement based materials - Cruz Moreno, Dulce María; Fajardo San Miguel, Gerardo del Jesús; Flores Vivián, Ismael; Cruz López, Arquímedes; Valdez Tamez, Pedro Leobardo (Revista ALCONPAT, 2017)
The effect of the introduction of silicon-based nanoparticles (NBS) prepared by the sol-gel method was studied. The introduction of NBS was induced for 72 hours during curing by using mortar specimens with a w/c ratio of 0.65 and a suspension prepared at [NBS] = 0.1% with respect to the volume of the curing water. Subsequently, the samples followed a period of immersion in potable water to promote the reaction of NBS inside mortar. Frequent measurements of electrical resistivity were made. Subsequently, a series of specimens were exposed in environments rich in Cl- or CO2. The results indicated a decrease in the penetration of aggressive agents into the mortar specimens. This coincides with increasing resistivity specimens treated with respect to the reference.